STUDY OF VITAMINS CONTENT OF MICROALGAE - Bakhodir Ismailkhodjayev; Bibiosiya Khalmurzaeva; Marat Satayev; Ravshanbek Alibekov (Academic Scientific Journal of Chemistry, 2019)
The efficiency of using microalgae biomass for practical purposes is determined by their physiological and biochemical features. The growth and development of algae are closely interrelated with external factors, under the influence of which the structural, functional and biochemical characteristics of the cell change. Selection of new highly active microalgae-producers of essential compounds in the natural conditions would expand the area of their practical application. The present work shows a comparative study of the amount of vitamins — provitamin A, vitamin C, vitamin E in the ten types and strains of green and Euglena microalgae, isolated from the local flora that grown in semi-industrial terms and under the open atmospheric conditions: Chlorella pyrenoidosa ChickYA-1-1; Scenedesmus obliquus YA-2-6; Ankistrodesmus angustus YA-3-1; Ankistrodesmus braunii; Chlamydomonas reinhardii YA-5-16; Chlamydomonas reinhardii 449; Euglena gracillis YA-4-17; Euglena YA-4-19; Dunaliella salina; Dunaliella minuta UA-5-10. It is shown that the vitamins content depends on the type of algae strain and the seasons, the duration of cultivation and the type of mixing. The developed biomass with a high content of vitamins allow to increase the biotechnological potential of microalgae that will provide an opportunity for the problems solving related to the provision of various sectors of the national economics by algae-rich raw materials: animal husbandry, poultry farming, fish farming, as well as food and pharmaceutical industries.